Study on Management Commitment to Service Quality: A Study on the Impact of Management Commitment on Service Quality in Indian Banks and Insurance Companies (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Out of the 800 distributedquestionnaires, we could collect 615 questionnaires. Only 530 of the returnedquestionnaires by whatever methods were found suitable for final analysis andwithout discrepancies. Remaining 85 questionnaires were rejected as they wereincomplete in one respect or the other. The detailed description of the samplecan be seen through Table 3.1. Out of the sample of 530respondents, 312 (150 government sector and 162 private/multinational)respondents were from banks and 218 (123 government sector and 95private/multinational) were from insurance companies. All respondent employees/managers were of Indian origin.